2019
DOI: 10.1038/s41416-018-0359-4
|View full text |Cite
|
Sign up to set email alerts
|

Drug sensitivity testing on patient-derived sarcoma cells predicts patient response to treatment and identifies c-Sarc inhibitors as active drugs for translocation sarcomas

Abstract: Background Heterogeneity and low incidence comprise the biggest challenge in sarcoma diagnosis and treatment. Chemotherapy, although efficient for some sarcoma subtypes, generally results in poor clinical responses and is mostly recommended for advanced disease. Specific genomic aberrations have been identified in some sarcoma subtypes but few of them can be targeted with approved drugs. Methods We cultured and characterised patient-derived sarcoma cells and evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…While important, there are widely recognized caveats in the use of long-established cell lines growing on rigid substrates, including genetic drift of cell lines under long-term culture [ 372 ] and non-physiologic response to 2D culture on plastic or glass. Several methods have been adopted to address these caveats, including analysis of primary patient-derived lines [ 373 ], and the development of 3D spheroid and organoid models [ 374 , 375 ]. Emphasizing the importance of modeling the tumor environment, Santoro and co-workers showed that culture of EwS cells on 3D scaffolds within a flow perfusion bioreactor promoted insulin-like growth factor-1 (IGF1) production and revealed shear stress-dependent resistance to an IGF-1R inhibitor [ 376 ].…”
Section: Scientific Perspectives On Clinical Enigmas Of Disseminated Ews Diseasementioning
confidence: 99%
“…While important, there are widely recognized caveats in the use of long-established cell lines growing on rigid substrates, including genetic drift of cell lines under long-term culture [ 372 ] and non-physiologic response to 2D culture on plastic or glass. Several methods have been adopted to address these caveats, including analysis of primary patient-derived lines [ 373 ], and the development of 3D spheroid and organoid models [ 374 , 375 ]. Emphasizing the importance of modeling the tumor environment, Santoro and co-workers showed that culture of EwS cells on 3D scaffolds within a flow perfusion bioreactor promoted insulin-like growth factor-1 (IGF1) production and revealed shear stress-dependent resistance to an IGF-1R inhibitor [ 376 ].…”
Section: Scientific Perspectives On Clinical Enigmas Of Disseminated Ews Diseasementioning
confidence: 99%
“…Taken together, these data underline the relevance of molecular and immunohistochemical interrogation for resistance-associated targets to improve SS treatment outcome by patient-specific pazopanib-based combination therapies. Moreover, implementation of the use of patient-derived ex vivo systems (e.g., primary cell cultures, 3D systems) is also expected to provide an opportunity to discover new mechanisms of drug resistance and improve personalized treatments [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…The selective drug sensitivity score (sDSS) of each compound was calculated using two independent reference databases; (i) our in‐house GBM drug screening database (up to n = 18 GBMs tested for drug sensitivity to the drug collection) and (ii) the FIMM database of drug sensitivity to normal bone marrow cells from healthy donors (n = 5). Control samples of normal bone marrow cells were obtained from informed and consenting donors, and the sampling was approved by the institutional ethics committee, as previously described [27,32]. The DSS from which the GBM reference database is based upon is available from previous reports by [13] us together with the additional files presented in this study.…”
Section: Methodsmentioning
confidence: 99%